Determinants Of Consumption Credit In North Sumatera - Priska Basariana Panggabean; Sitompul, Thomson (SEAN Institute, 2024)
The purpose of this study was to examine the impact of interest rates and inflation on the demand for consumer loans at commercial banks in North Sumatra and provide a comprehensive understanding of how these economic variables affect consumer borrowing behavior. The data for this research is limited to the years 2015-2022, with observations taken quarterly (Quarter 1, Quarter 2, Quarter 3, and Quarter 4). The unit of analysis is the region of North Sumatera, resulting in a total of 32 samples.The regression model developed in this study reveals that interest rates have a negative impact on the demand for consumer credit in North Sumatera. Specifically, as interest rates increase, the cost of borrowing rises, leading to a decrease in consumer credit demand. Furthermore, the study finds that inflation also negatively influences the demand for consumer credit. An increase in inflation erodes the purchasing power of consumers, which in turn reduces their ability to take on additional debt.By understanding these relationships, the research provides valuable insights for policymakers and financial institutions. It highlights the importance of monitoring and managing interest rates and inflation to maintain a stable demand for consumer credit, which is crucial for the overall economic health of North Sumatera.